2013
DOI: 10.3390/ijerph10093843
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Acrylamide in Exposed Workers

Abstract: Acrylamide (ACR) is a water-soluble chemical used in different industrial and laboratory processes. ACR monomer is neurotoxic in humans and laboratory animals. Subchronic exposure to this chemical causes neuropathies, hands and feet numbness, gait abnormalities, muscle weakness, ataxia, skin and in some cases, cerebellar alterations. ACR neurotoxicity involves mostly the peripheral but also the central nervous system, because of damage to the nerve terminal through membrane fusion mechanisms and tubulovescicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(129 citation statements)
references
References 63 publications
8
113
0
6
Order By: Relevance
“…Additionally, pain, paresthesias, loss of balance, and truncal ataxia may appear in some cases [46]. The initial symptoms are skin rash and hands, cramps, sweating, and peeling.…”
Section: Toxic Effectsmentioning
confidence: 99%
“…Additionally, pain, paresthesias, loss of balance, and truncal ataxia may appear in some cases [46]. The initial symptoms are skin rash and hands, cramps, sweating, and peeling.…”
Section: Toxic Effectsmentioning
confidence: 99%
“…Its wide spread application is associated with pollution and health risks [10]. It is also a common contaminant in foods prepared by cooking at high temperatures [11]. Even though, occupational ACR exposure in humans is recognized as the primary risk factor, there is a growing concern about the potential health effects of low sub-chronic ACR exposure through commonly consumed thermally processed foods [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, the results provided insight into the inhibitory effects and the possible ligand-binding mechanism of acrylamide on CK . Pennisi et al (2013) showed that acrylamide-exposed workers presented high prevalence of paresthesia in hands and legs, cramping in legs, poor blood circulation in fingers, skin irritation and peeling of skin on the hands, headache and breathlessness. The acrylamide induced neurotoxicity diminished ATP-ase activity while enhancing activity of acetilcholinesterase and dopamine depletion.…”
Section: Epidemiological Evidence Of Risk From Consumption Of Acrylammentioning
confidence: 99%